STUDIES ON THE BIOLOGY OF COILIA DUSSUMIERI (CUV. & VAL.) - Bal, D V; Joshi, M S (Indian Journal of Fisheries, 2015)
Cdilia dussumieri, popularly known as mandeli, is one of the common food fishes occurring in Bombay. This fish is usually taken along with other fish in the catches of the Dol, a specialised bag-net operated along the Bombay Coast. It reaches a maximum size of 200 mm. and is an important item of food of the poor and middle-class people. The information availaljle in literature on this species relates to the systematic position and distrilution (Day, 1878), the structure of the egg and its development (Delsman, 1932), a preliminary study of the food and feeding habits at different growth stages (Bapat and Bal, 1950), the development and regeneration of the caudal fin (Jones and Menon, 1952) and the stages of maturity in different months of the year (Palekar and Karandifcar, 1953). Recently Joshi and Bal (1953) have given an account of its skeletal system.